Changes in Mountain Birch Forests and Reindeer Management:Comparing Different Knowledge Systems in Sápmi, Northern Fennoscandia - Forbes, Bruce C.; Turunen, Minna; Soppela, Päivi; Rasmus, Sirpa; Vuojala-Magga, Terhi; Kitti, Heidi (Polar Record, 2020)
Mountain birch forests in the northern areas of Sápmi, the Saami homeland, serve as pastures for semi-domesticated reindeer. Recent reindeer management of the area has, to date, proceeded with little involvement of reindeer herders or their knowledge. To get more in-depth understanding of recent changes, we present together herders’ knowledge and scientific knowledge concerning the impacts of herbivory and climate change on mountain birch forests in three Saami communities in Norway and in Finland. Most of the herders interviewed reported changes in weather during the preceding decades. Herders agreed that the canopy and understorey of mountain birch forests have changed. The observed transformations in the quality of pastures have increased the financial costs of reindeer husbandry. Our study demonstrates that herders have practical knowledge of the present state and recent changes of birch forests, and of the responses of reindeer caused by these. This knowledge generally coincides with scientific knowledge. We call for better integration of knowledge systems and a better protocol for co-production of knowledge as it relates to more adaptive future reindeer management regimes. Such integration will facilitate understanding of cultural adaptation within rapidly changing social-ecological systems in which sustainable reindeer husbandry continues to be an important livelihood.